THE INFLUENCE OF HOSPITAL FACILITIES, NURSING SERVICES, AND PATIENT SATISFACTION ON OUTPATIENT REVISIT INTENTION (A CASE STUDY AT DEMANG SEPULAU RAYA REGIONAL GENERAL HOSPITAL, CENTRAL LAMPUNG REGENCY) - Tiara Cornela Azqinar; Vip Paramarta; R. Ricky Agusiady (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of hospital facilities, nursing services, and patient satisfaction on outpatient revisit intention at Demang Sepulau Raya Regional General Hospital, Central Lampung Regency. The research focuses on understanding outpatient behavior in deciding to reuse healthcare services as an indicator of service quality performance in regional hospitals. A quantitative approach was employed using a survey method involving ninety-one outpatient respondents from the general clinic. Data were collected through structured questionnaires and analyzed using SPSS software after fulfilling the required statistical assumptions. All research instruments were declared valid and reliable, indicating their suitability for further analysis. The results show that hospital facilities and nursing services play an important role in shaping patient satisfaction. Patient satisfaction subsequently becomes the most decisive factor influencing outpatient revisit intention. Both partially and simultaneously, hospital facilities, nursing services, and patient satisfaction are interrelated and significantly influence patients’ decisions to return to the same hospital. These findings confirm that positive service experiences not only affect patient perceptions but also contribute to the development of long-term patient loyalty. This study recommends that regional hospital management continuously improve the quality of facilities and strengthen nurses’ competencies and service attitudes in a sustainable manner. Such efforts are expected to maintain patient satisfaction and consistently encourage outpatient revisit intentions.